Establishing workability asphalt mixtures - Iriciuc, S C; Gălușcă, N I; Pleșcan, C (IOP Publishing, 2020)
The article shows the need to improve repair technologies for bituminous pavements especially during the cold season. As a result of laboratory tests, it was found the need for other attempts. These are attempts on storable asphalt mixtures workability at various temperatures for the installation period, but also for the storage period. Through the laboratory tests was shown the complex interaction between mechanical behaviour of asphalt mixtures and variability factors acting on the road structure, this complex framework is determined by fundamental mechanical properties that influence long-term performance.